Evaluasi dan Perancangan Perbaikan Desain Antarmuka Pengguna Situs Web Haiwanita.com - G. Tulus Hari Ramadhan; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The website haiwanita.com is one of the information media that discusses women, from the latest information about the health of babies, children, adolescents, adults to menopause. Based on the latest knowledge which provides useful information to increase the knowledge of readers, especially women. This counseling is provided by experts in their fields. However, 5 women who use this website still do not feel comfortable using this website, because the news layout is close, the repetition of the same news, the ad layout is not good so that the level of website usability is not good. To produce a website Interface that can be more easily understood and used by users, the Human Centered Design (HCD) approach is used which involves 5 users as respondents. This study uses 2 aspects of usability, namely aspects of effectiveness and efficiency. These two aspects are used in the evaluation before and after the Interface design is updated. The results of the comparisons made get the results of the increase in the two aspects used. In the efficiency aspect, there was an increase of 00: 19.47 seconds, the effectiveness aspect increased by 28%.